Can Aspirin Use Be Associated With the Risk or Prognosis of Bladder Cancer? A Case-Control Study and Meta-analytic Assessment - Fan, Bo; Mohammed, Alradhi; Huang, Yuanbin; Luo, Hong; Zhang, Hongxian; Tao, Shenghua; Xu, Weijiao; Liu, Qian; He, Tao; Jin, Huidan; Sun, Mengfan; Sun, Man; et al. (Frontiers in Oncology, 2021)
Aspirin, widely used to prevent cardiovascular disease, had been linked to the incidence of bladder cancer (BCa). Existing studies focusing on Chinese populations are relatively rare, especially for Northeast China. Meanwhile, relevant studies on the effects of aspirin on the occurrence or prognosis of BCa are inconsistent or even controversial. First, in the case control study, logistic regression analysis was used to investigate the association between aspirin intake and risk of BCa including 1121 patients with BCa and the 2242 controls. Subsequently, Kaplan-Meier curve and Cox regression analyses were applied to explore the association between aspirin intake and clinicopathological factors which may predict overall survival (OS) and recurrence-free survival (RFS) of BCa patients. Finally, we quantificationally combined the results with those from the published literature evaluating aspirin intake and its effects on the occurrence, outcome of surgery and prognosis of BCa by meta-analysis up to May 1, 2021.Our case-control study demonstrated that the regular use of aspirin was not associated with a reduced incidence of BCa (P=0.175). Stratified analyses of sex showed that aspirin intake did not lead to a lower risk of BCa in female patients (P=0.063). However, the male population who regularly took aspirin had a lower incidence of BCa (OR=0.748, 95% CI= 0.584-0.958, P=0.021). Subgroup analyses stratified by smoking found a significant reduction in the risk of BCa in current smokers with aspirin intake (OR=0.522, 95% CI=0.342-0.797, P=0.002). In terms of prognosis of BCa, patients with a history of aspirin intake did not had a markedly longer OS or RFS than those with no history of aspirin intake by Kaplan-Meier curves. Stratified analysis by sex showed no correlation between aspirin intake and the recurrence or survival of BCa for either male or female patients. However, in people younger than 68, aspirin intake seemed to have prolonged effects for overall survival (HR=3.876; 95% CI=1.326-11.325, P=0.019). Then, we performed a meta-analysis and the combined results from 19 articles and our study involving more than 39524 BCa cases indicated that aspirin intake was not associated with the occurrence of BCa (P=0.671). Subgroup analysis by whether regular use of aspirin, by the mean duration of use of aspirin, by sex, by smoking exposure, by research region and by study type also supported the above results. In terms of the impact of aspirin intake on the prognosis of patients with BCa, 11 articles and our study involving 8825 BCa cases were eligible. The combined results showed that patients with aspirin intake did not have significantly influence on survival, recurrence, progression and metastasis than those without aspirin intake. On the whole, both our retrospective study and literature meta-analysis suggested a lack of a strong relevant association between the use of aspirin and the incidence or prognosis of BCa. Thus, additional long-term follow-up prospective research is warranted to clarify the association of aspirin with BCa incidence and prognosis.